A new intervention for people with borderline personality disorder who are also parents: a pilot study of clinician acceptability. Issue 1 (December 2016) - McCarthy, Kye; Lewis, Kate; Bourke, Marianne; Grenyer, Brin
Abstract Background Engaging parents who have a personality disorder in interventions designed to protect children from the extremes of the disorder supports both parenting skills and healthy child development. In line with evidence-based guidelines, a 'Parenting with Personality Disorder' brief intervention was developed, focusing on child safety, effective communication and parenting strategies. Method Ratings of acceptability for the brief intervention model were given by 168 mental health clinicians who attended training. Changes in clinician attitudes, knowledge and skills were also assessed following training. Results Providing clinicians treating personality disorder clients with additional skills to address parenting was well received and filled a gap in service provision. Clinicians reported improvements in clinical skills, knowledge, willingness and confidence to intervene in parenting issues with clients. Qualitative responses endorsed three major modes of learning: case study analysis, reflective learning activities, and skills-based intervention practices. Conclusions Current treatment guidelines emphasise addressing parenting, but no evidence-based therapy includes specific parenting skills. This brief intervention model improved skills, efficacy and willingness to intervene. This approach can be readily added to current evidence-based therapy protocols and promises to improve client functioning and protect children from the extremes of the disorder. Clinical trials are now required to validate the approach in the field.